Effect Of A Lactobacilli Probiotic On Longevity And Mobility Of Male Drosophila Melanogaster With Alzheimer’s Disease - Lim, Chin Peng (Universiti Sains Malaysia, 2020)
This study aimed to evaluate the effect of Lactobacillus fermentum DR9 on the longevity of AD flies and to study the effect of Lactobacillus fermentum DR9 on the mobility of AD flies. Longevity test and climbing test were conducted in triplicates to determine the effect of treatment using Lactobacillus fermentum DR9 in alleviating the lifespan shortening and mobility impairment of AD flies respectively.